Study on the Relationship between Unexplained Recurrent Abortion and HLA-DQ Gene Polymorphism. (29th August 2022) - Tang, Jie; Zhu, Jichao; Shu, Longwen; Huang, Xiaohong; Ma, Siming
Abstract : Objective . The study aimed to investigate the relationship between human leukocyte antigen (HLA-DQB1) gene variants and recurrent miscarriage. Methods . HLA-DQ gene polymorphisms (PCR-SSP) were detected in 50 couples with recurrent miscarriage (URSA group) and 30 couples with normal births (control group) using sequence-specific primer-guided polymerase chain reaction. Results . The frequency of the DQB1 ∗ 0303 allele in the URSA group (21.50%) was substantially higher than that of the control group (11.67%) (P = 0.0260 0.05, RR = 1.754); however, the frequency of the DQB1 ∗ 0302 allele in the URSA group (4.00%) was substantially lower than that of the control pair (10.00%) (P = 0.0318 0.05, RR = 0.400); the frequency of sharing one allele was 46.00% (23/50) in the URSA group and 0.00% (0/30) in the normal control group; the frequency of sharing two alleles was 40.00% (2/50) in the URSA group and 43.33% (13/30) in the normal control group, with no significant difference between the two groups. Conclusion . For the Zhejiang population, HLA-DQB1 ∗ 0303 may be a susceptibility gene for recurrent miscarriage, while HLA-DQB1 ∗ 0302 may be protective against recurrent miscarriage, especially for women.